Performance Study of IEEE 802.15.4 under OPNET Modeler for Wireless Sensor Networks - Rania Khadim; Mohammed Erritali; Abdelhakim Maaden (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
The IEEE 802.15.4 protocol has recently been adopted as a communication standard for low-rate wireless personal area networks (LR-WPANs) due to its low data rate, low power consumption and low cost of Wireless Personal Area Networks. This protocol is quite flexible for a wide range of applications if appropriate tuning of its parameters is carried out. Importantly, the protocol also provides real-time guarantees by using the Guaranteed Time Slot (GTS) mechanism. Indeed, the GTS mechanism is quite attractive for Wireless Sensor Network (WSN) applications. The main objective of this paper is to investigate the performance of BPSK (Binary phase shift keying) and QPSK (Quadrature phase shift keying) modulation techniques. Investigations have been reported to compare the performance of the two modulation schemes. Here modulation schemes have been identified which gives significant performance improvement over the other based on network output load, energy consumption and power reception at the WPAN devices. The results have been presented Pan_Coordinator, GTS and Non GTS End Device (CAP device) of Wireless Sensor Network (WSN).